High fidelity simulation of a drone propeller in hover - Dorange, A.; Benoit, C.; Garnier, E.; Peron, S. (My University, 2022)
Even though drones were initially developed for military purposes during World War I, they are now being widely used due to their large range of applications. Technological improvements enabled their use for many private and professional applications. Although drones have been widely studied in the field of flight control, their aerodynamic behavior is yet to be completely understood. Recently, some aerodynamic and aeroacoustic studies have been performed and published using Computational Fluid Dynamics (CFD) methods. Among these, some simulations use Reynolds-Averaged Navier-Stokes (RANS) models and others Large Eddy Simulation (LES) models and they tend to rely on 3D scanned geometries of commercial propellers. There are plenty of drones flying around the world (the US Federal Aviation Administration has registered 865 thousands of drones across the US in May 2022) and a lot of manufacturers. However, limited information on the aerodynamics of industrial propellers can be found.